2007
DOI: 10.1186/ar2214
|View full text |Cite|
|
Sign up to set email alerts
|

The PTPN22 1858C/T polymorphism is associated with anti-cyclic citrullinated peptide antibody-positive early rheumatoid arthritis in northern Sweden

Abstract: The PTPN22 1858C/T polymorphism has been associated with several autoimmune diseases including rheumatoid arthritis (RA). We have shown that carriage of the T variant (CT or TT) of PTPN22 in combination with anti-cyclic citrullinated peptide (anti-CCP) antibodies highly increases the odds ratio for developing RA. In the present study we analysed the association between the PTPN22 1858C/T polymorphism and early RA in patients from northern Sweden, related the polymorphism to autoantibodies and the HLA-DR shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 23 publications
6
66
0
Order By: Relevance
“…Five RA case-control studies based on anti-CCP antibody status were recruited for the meta-analysis. 18,22,28,40,101 The results showed a strong association between the T allele and anti-CCP þ RA (OR ¼ 1.78; 95% CI ¼ 1.59-2.01, Po1.00 Â 10 Figure 1b).…”
Section: Diseases Showing No or Weak Association With Ptpn22mentioning
confidence: 91%
See 2 more Smart Citations
“…Five RA case-control studies based on anti-CCP antibody status were recruited for the meta-analysis. 18,22,28,40,101 The results showed a strong association between the T allele and anti-CCP þ RA (OR ¼ 1.78; 95% CI ¼ 1.59-2.01, Po1.00 Â 10 Figure 1b).…”
Section: Diseases Showing No or Weak Association With Ptpn22mentioning
confidence: 91%
“…The highest T allele frequency (17.5%) was reported in northeast Russia, 14 followed by Finland (15.4%), 15 Ukraine (14.1%) 16 and Estonia (13.9%). 17 The frequency decreased toward the west, showing 11-13% in Poland, [18][19][20] 10-12% in Sweden, [21][22][23] Norway [24][25][26] and Germany, 24,[27][28][29] 11.7% in Croatia, 10-11% in the Czech Republic, 30,31 10.7% in Slovakia, 32 9.2% in Denmark, 33 and 8-10% in the UK [34][35][36][37][38][39] and the Netherlands. 24,[40][41][42] The decrease in the frequency toward the south was dramatic, with 7.75% in Hungary, 43 7.23% in Belgium, 7-8% in France, 44,45 5-7% in Spain 46-48 and 4.1% in Romania.…”
Section: Frequency Of the Ptpn22 Minor Allelementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic differences may be the reason for this relatively lower prevalence. The protein tyrosine phosphatase (PTPN22) 1858C/T polymorphism has been reported to be associated with anti-CCP antibody positivity in early RA in a study from Northern Sweden (Kokkonen et al 2007). However, preliminary data from a recent study from Turkey has shown that PTPN22 polymorphism is not related with RA (the data presented in the 2007 Annual Turkish National Rheumatology Congress).…”
Section: Discussionmentioning
confidence: 99%
“…However, as genetic differences and environmental factors may alter the anti-CCP antibody positivity (van Gaalen et al 2004;Furuya et al 2007;Kokkonen et al 2007;Verpoort et al 2007), the aims of the present study were directed to evaluate the frequency of anti-CCP antibody positivity in Turkish patients Stored sera were tested for anti-CCP antibodies by ELISA using a second-generation commercial assay kit (Euroimmun, Lubeck, Germany). The ELISA was carried out according to the manufacturer's instructions with a cut-off value of 5.01 units.…”
Section: Participants and Methodsmentioning
confidence: 99%